Skill Level in Tennis Serve Return Is Related to Adaptability in Visual Search Behavior - Rosker, Jernej; Majcen Rosker, Ziva (Frontiers in Psychology, 2021)
Analyzing visual search strategies in tennis is primarily focused on studying relations between visual behavior and tennis performance. However, diverse movement characteristics amongst different servers suggest the importance of adjusting one’s visual search strategies while playing against different opponents. The aim of this study was to analyze whether visual search strategies can be attributed to individual server and returning player during tennis serve return, or return performance. Seventeen tennis players were enrolled in the study (5 international players and 12 national players) producing a sample of 1020 returns measured with mobile eye trackers. Random forest machine learning model was used to analyze the ability to classify the returning player (area under the curve - AUC .953), individual server (AUC .686) and return performance category (AUC .667) based on the location and duration of the focal vision fixation. In international tennis players higher predictability of the server was observed as compared to national level players (AUC .901 and .834 respectively). More experienced tennis players presented with higher ability to adjust their visual search strategies to different servers. International players also demonstrated anticipatory visual behavior during the tossing hand movement and superior information pick-up during the final phases of server’s stroke.